Appraisal of Structural, Thermal, and Optical Properties of Novel Bluish-Violet Light-Emitting Cyclometallated Iridium (III) (Cl-H-DPQ)2Ir(acac) Complex for OLED Devices. (26th July 2021) - Khotele, Neha; Kalyani, N. Thejo; Pode, Ramchandra; Dhoble, S. J.
Abstract : Synthesis and evaluation of structural, thermal, and optical properties of a novel bluish-violet light-emitting cyclometallated Iridium (Ir 3+ ) complex [(Cl-H-DPQ)2 Ir(acac)] containing 4-(6-chloro-4-phenylquinolin-2-yl) phenol as main ligand and acetyl acetone (acac) as ancillary ligand by employing Friedlander reaction at 105 °C is reported. X-ray diffraction of the complex reveals its crystalline nature and scanning electron microscopy illustrates polygonal morphology within the nm range. FTIR spectra confirms the structure formation and molecular bonding of the synthesized complex. DTA/TGA curves reveal its thermal stability to about 252 °C demonstrating its potential at elevated temperatures. UV–vis optical absorption and photoluminescence spectra were carried out in solid state form and in various organic solvents ranging from basic to acidic media. This facilitated estimation of the energy band gap and Stokes shift in various organic solvents. When excited at 350 nm light, the complex emits prominent bluish-violet light peaking at 468 nm in the solid-state form. However, it shows a bathochromic shift in acidic media and a hypsochromic shift in basic media. CIE chromaticity coordinates ( x, y ) of (Cl-H-DPQ)2 Ir(acac) complex in solid state form was found to be (0.2631, 0.2358), and in acetic acid and formic acid they were found to be (0.325, 0.159) and (0.402, 0.198), respectively, while in chloroform and dichloromethane they were found to be (0.1616, 0.043) and (0.1756, 0.062), respectively. The Stokes shift was found to be in the range of 6480–15, 719 cm −1 in various acidic and basic solvents. The solvent sensitivity to chromophore was probed by a Lippert–Mataga plot. These results reflect the potential of the (Cl-H-DPQ)2 Ir(acac) complex as a bluish-violet light-emitting material for organic light-emitting diodes, displays, and solid-state lighting.